Pemaknaan Ihdad Bagi Perempuan Yang Beriddah Di Era Digital - Aminudin, Aminudin; Nurasiah, Nurasiah; Sukiati, Sukiati (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2024)
This study aims to find out ihdad for women who are still in the iddah period of death by their husbands in the digital era. For women whose husbands die, they still actively use social media, of course this will contradict the classical rule that during the iddah period of four months and ten days, the wife expresses her grief by not wearing makeup, not blinking her eyes, not wearing perfume and not leaving the house except on certain business. Even though in fact she does not leave the house nowadays, by uploading photos or videos on social media pages, more people will see. The question is how to use social media when women are in the ihdad period. This research is qualitative with a normative study approach, which is research that is directed and focused on collecting library materials, which have to do with the problem of ihdad. The results of this study conclude that women who are left dead by their husbands are not allowed to use social media social media as a medium to express feelings, share daily activities, upload photos or videos of themselves for four months and ten days, to avoid negative things and can cause lust for men. Keywords: Analysis, Ihdad, for Women, Digital Age, Islamic Law